2022
DOI: 10.1186/s12885-022-09649-3
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of potentially significant drug-drug, drug-herb, and drug-food interactions among cancer patients receiving anticancer drugs

Abstract: Introduction During the cancer treatment path, cancer patients use numerous drugs, including anticancer, supportive, and other prescribed medications, along with herbs and certain products. This puts them at risk of significant drug interactions (DIs). This study describes DIs in cancer patients and their prevalence and predictors. Methods A cross-sectional study design was used to achieve the study objectives. The study was carried out in two cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In a US study to evaluate drug information knowledge retention, the pharmacists' knowledge decreased one year after the educational courses were provided; therefore, continual education is a key to safe pharmacy practices 9 . On the other hand, another American study revealed a significant improvement in the knowledge and score of pharmacists in drug interactions after the educational programs 23 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a US study to evaluate drug information knowledge retention, the pharmacists' knowledge decreased one year after the educational courses were provided; therefore, continual education is a key to safe pharmacy practices 9 . On the other hand, another American study revealed a significant improvement in the knowledge and score of pharmacists in drug interactions after the educational programs 23 .…”
Section: Discussionmentioning
confidence: 97%
“…The study's findings revealed that community pharmacists in Palestine have an acceptable knowledge about DDI compared to other regional studies in Saudi Arabia, Lebanon, and Jordan., 12,13,22 , even though a study describing the prevalence of DIs in cancer patients in Palestine showed a prevalence of DDIs was 88.1% 23 . This is incongruent with a national study that evaluated community pharmacists' knowledge about the potential DFI, where the results showed they did not have the appropriate DFI knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, combining multiple drugs can generate drug interactions in both pharmacodynamics and pharmacokinetics. A comprehensive evaluation has shown that the number of potential DDIs significantly increases with the number of comorbidities and drugs used in cancer patients ( Koni et al, 2022 ). This can impact treatment outcomes by increasing the incidence of drug-related adverse reactions or reducing efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, combining multiple drugs may alter the drug profiles on pharmacodynamics and pharmacokinetics attributed to drug interactions. In a comprehensive evaluation [ 36 ], the prevalence of DDIs was 88.1% in cancer patients, which increased with the number of comorbidities and drugs used. Consequently, it diminishes the patient’s quality of life by reducing efficacy or increasing the drug-related adverse effects.…”
Section: Discussionmentioning
confidence: 99%